Integrating newcomers for success and personal initiative in resilient engagement (INSPIRERX23) 2024 / Siti Nur Aisyah Che Zamri and Muhammad ‘Izzuddin Zamery - Che Zamri, Siti Nur Aisyah; Zamery, Muhammad ‘Izzuddin (Faculty of Pharmacy, 2024)
The eagerly awaited INSPIRERX23 event for new students of the Faculty of Pharmacy took place on October 13th, 2024, with the remarkable participation of 243 students. Organized by the Society of Pharmacy Students (SOPHYS) and the Faculty of Pharmacy Student Secretariat (SMF), this year’s theme was the exciting “Zombie Apocalypse.”